The Buffering Effect of Spirituality at Work on the Mediated Relationship between Job Demands and Turnover Intention among Teachers - Charzyńska, Edyta (Religions, 2021)
The purpose of this study was to examine whether spirituality at work moderates the direct and indirect (through burnout) effects of quantitative and emotional job demands on turnover intention among teachers. The sample consisted of 952 Polish primary and secondary school teachers. Burnout mediated the relationship between both types of job demands and turnover intention. In the model with quantitative job demands as an independent variable, spirituality at work moderated the second stage path of the indirect effect, i.e., the relationship between burnout and turnover intention (b = −0.022; SE = 0.004; p < 0.001; β = −0.14). In the model with emotional job demands as an independent variable, spirituality at work moderated the first and second stage paths of the indirect effect, i.e., the relationship between emotional job demands and burnout (b = −0.001; SE = 0.001; p = 0.032; β = −0.05) and the relationship between burnout and turnover intention (b = −0.020; SE = 0.004; p < 0.001; β = −0.14). In both models, the indirect effect of job demands on turnover intention through burnout weakened as spirituality at work increased. The results of the study support the inclusion of spirituality at work as a subcategory of personal resources in studies using the job demands-resources model.